2010
DOI: 10.1002/cssc.201000258
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Improvement of the Photocatalytic Activity of Ga2O3 Towards the Overall Splitting of H2O

Abstract: . Various kinds of photocatalytic systems have been studied for this reaction, with an aim to develop new and effective photocatalysts. [1,2] However, thus far their photocatalytic performances, that is, not only their photoresponse but also their activity, have been insufficient for further applications, such as H 2 production from H 2 O under solar irradiation. Therefore, improving the activity as well as the photoresponse towards H 2 O splitting are important problems that need to be solved.When attempting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 17 publications
2
79
0
Order By: Relevance
“…The results suggest a strong synergetic promoting effect between the doping and the co-catalytic components, which cannot be explained by simple additive combination of the two contributions. The catalytic activities reported here are in good agreement with those reported for Sakata's commercial Ga 2 O 3 modification series 7 (ca. 50% of the reported batch reactor activity for Zn/Rh-Cr modified sample) with the exception of a lower oxygen evolution for bare Ga 2 O 3 and Ga 2 O 3 Zn samples in our study (very close to the detection limit as shown in Table 1), although differences in reactor design, catalyst amount and lamp power do not allow a strict comparison.…”
Section: Slurry Reactor Testing Of Ga Ta and Ti Based Photocatalystssupporting
confidence: 88%
See 2 more Smart Citations
“…The results suggest a strong synergetic promoting effect between the doping and the co-catalytic components, which cannot be explained by simple additive combination of the two contributions. The catalytic activities reported here are in good agreement with those reported for Sakata's commercial Ga 2 O 3 modification series 7 (ca. 50% of the reported batch reactor activity for Zn/Rh-Cr modified sample) with the exception of a lower oxygen evolution for bare Ga 2 O 3 and Ga 2 O 3 Zn samples in our study (very close to the detection limit as shown in Table 1), although differences in reactor design, catalyst amount and lamp power do not allow a strict comparison.…”
Section: Slurry Reactor Testing Of Ga Ta and Ti Based Photocatalystssupporting
confidence: 88%
“…A common productivity trend was consistently found in the order of bare oxide < Zn < Rh-Cr < Zn/Rh-Cr modified materials. The intrinsic activity of the metal oxides was also found to be extremely important, as the photocatalytic activity 7 were reached testing Ga 2 O 3 materials. Tantalum based oxides also displayed excellent activity but with an order of magnitude below the promoted Ga 2 O 3 materials.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The contrast in the characterization and interpretation may arise from the use of different types of SrTiO 3 as supports and the different amounts and temperatures used for the loading and treatment of nickel species as cocatalysts. NaTaO 3 doped with La [44] and Ga 2 O 3 doped with Zn [45] exhibit the highest known QY water-splitting rates under UV irradiation after successful catalyst loading with NiO and Rh 2-y Cr y O 3 , respectively. Both NiO and Rh 2-y Cr y O 3 cocatalysts improved hydrogen evolution activity, which is essential for achieving overall water splitting.…”
Section: Electrocatalytic Hydrogen and Oxygen Evolution Reactionsmentioning
confidence: 99%
“…[25][26][27] Recently, it was found that the activity of Ga 2 O 3 -based photocatalyst could be enhanced by doping with foreign ions such as Zn 2+ . 21,28 However, doping Ga 2 O 3 with Zn 2+ ions can also result in a decrease of photocatalytic H 2 evolution activity. 23 Doping Ga 2 O 3 with other ions often leads to a decrease of photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%